CP-149 Redesign of the management model and pharmaceutical care of patients with hepatitis C virus infection. (14th February 2016) - Menchen, B; Folguera, C; De rivas, A; Saavedra, V; Sanchez, A
Abstract : Background: The new direct antiviral agents (DAA) have represented a breakthrough in the treatment of hepatitis C virus infection (HCV). After the approval of the DAA, public hospitals had the challenge of treating an increased number of patients in a short time, forcing the hospital pharmacy to redesign the working procedures. Purpose: To redesign the management model and pharmaceutical care of patients with HCV and evaluate the results. Material and methods: The multidisciplinary team was formed of a doctor, nurse and pharmacist. It was necessary to establish an appointment system, in order to avoid unscheduled visits, optimising working hours and offering the patient better care. At the same time, this organisation helped us to estimate the stock of drugs. The role of the pharmacist was to provide information on the objective of the treatment, administration and preservation, interactions and to promote adherence. The activity performed was registered in the medical record. Patient satisfaction was measured with a survey: before setting up the new system and 6 months after. The main points were global quality, attention and information received. All patients were included in a database to provide periodic information (treatment duration, genotype, fibrosis, pretreatments, final result and packaging consumed). Results: After 6 months, 372 patients had been treated with 49 direct interventions. 30% of the interventions were about interactions, 21% adverse effects, 6% non-adherence, 2% medication errors and 10% other. 99% of patients attended the appointment which allowed optimising the activity of the pharmacist, concentrating assistance into 3 days a week and releasing time to assist in other areas. The record of activity in the patient's medical record, so as to inform the doctors, permitted objective activity data to be presented to hospital management. Regarding patient satisfaction, it increased by 17% for the overall quality perceived and 32% for satisfaction with the information received. Conclusion: Establishment of an appointment system for patients instead of unscheduled visits, as well as the coordination of the healthcare team, enhanced patient satisfaction and optimised the working hours of the pharmacists, increasing the time to develop new projects, and to become a clinical service in the managing of the hospital. No conflict of interest.